The faithful librarian : essays on Christianity in the profession - Trott, Garrett B., 1973-; Smith, Gregory A., 1972- (Jefferson, North Carolina : McFarland & Company, Inc., 2019)
"What do Christianity and librarianship have in common? Netherlands Prime Minister and theologian Abraham Kuyper (1837-1920) was among the first in the modern era to attempt to rejoin the dichotomy of sacred vs. secular study when he said, "no single piece of our mental world is to be hermetically sealed off from the rest." Over the years a number of publications have followed Kuyper's lead yet little has been written on the subject since Greg A. Smith's notable Christian Librarianship (2002). Building on Smith's work, this volume seeks to bridge the sacred/secular divide with an exploration of how Christianity and the gospel are manifested through the profession of librarianship."--
Integrative pastoral librarianship in a flipped church: equipping laity for ministry with missional faith learning / Rebecca Klemme Eliceiri -- With quiet diligence: how Claude Elbert Spencer formed an archival tradition in the Stone-Campbell movement / McGarvey Ice -- Libraries in the new creation: Christian librarianship as an extension of the Christian temple and priesthood / Jacob W. Gucker -- In a manner worthy of God: hospitality and the Christian librarian / Denise D. Nelson -- Information overload, information anxiety and theological ethics / Paul A. Hartog -- Scholarship as conversation: using a shared research method (ALEA) to help students seek truth and wisdom in a post-truth world / Patricia R. Harris, Michelle Norquist, Dianne Zandbergen and Andrew Zwart -- Knowledge, understanding, wisdom: a biblical model of information literacy / Jeff Gates -- Faith, freedom, and information: a Christian perspective on intellectual freedom / Steve Silver -- Communities of scholarship, communities of faith: the academic library as place / Nancy Falciani-White -- Loving your co-worker as Christ expects: personnel practices through the eyes of faith / Esther Gillie -- Discerning and following Christ's call to leadership / Nadine P. Ellero -- Christian faith and its impact on library interpersonal relationships and professionalism / Dana M. Caudle -- The relational interaction: a new look at glorifying God through a reference interview / Garrett B. Trott -- The information therapist is in / Robin R. Hartman -- Holy listening in reference work: a sacred aspect of the Christian librarian's calling / Cynthia Strong.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Christian librarians -- Religious life; Libraries -- Religious aspects -- Christianity; Bibliothécaires chrétiens -- Vie religieuse; Bibliothèques -- Aspect religieux -- Christianisme; Language Arts & Disciplines / Library & Information Science; Libraries -- Religious aspects -- Christianity